Defibrotide mitigates endothelial cell injury induced by plasmas from patients with COVID-19 and related vasculopathies. Issue 225 (May 2023) - Elhadad, Sonia; Redmond, David; Tan, Adrian; Huang, Jenny; Rodriguez, Beatriz Lorenzo; Racine-Brzostek, Sabrina E.; Subrahmanian, Sandeep; Ahamed, Jasimuddin; Laurence, Jeffrey
Abstract: Background and objectives: COVID-19 progression is characterized by systemic small vessel arterial and venous thrombosis. Microvascular endothelial cell (MVEC) activation and injury, platelet activation, and histopathologic features characteristic of acute COVID-19 also describe certain thrombotic microangiopathies, including atypical hemolytic-uremic syndrome (aHUS), thrombotic thrombocytopenic purpura (TTP), and hematopoietic stem cell transplant (HSCT)-associated veno-occlusive disease (VOD). We explored the effect of clinically relevant doses of defibrotide, approved for HSCT-associated VOD, on MVEC activation/injury. Methods: Human dermal MVEC were exposed to plasmas from patients with acute TMAs or acute COVID-19 in the presence and absence of defibrotide (5μg/ml) and caspase 8, a marker of EC activation and apoptosis, was assessed. RNAseq was used to explore potential mechanisms of defibrotide activity. Results: Defibrotide suppressed TMA plasma-induced caspase 8 activation in MVEC (mean 60.2 % inhibition for COVID-19; p = 0.0008). RNAseq identified six major cellular pathways associated with defibrotide's alteration of COVID-19-associated MVEC changes: TNF-α signaling; IL-17 signaling; extracellular matrix (ECM)-EC receptor and platelet receptor interactions; ECM formation; endothelin activity; and fibrosis. Communications across these pathways were revealed by STRING analyses. Forty transcripts showing the greatest changes induced by defibrotide in COVID-19 plasma/MVEC cultures included: claudin 14 and F11R (JAM), important in maintaining EC tight junctions; SOCS3 and TNFRSF18, involved in suppression of inflammation; RAMP3 and transgelin, which promote angiogenesis; and RGS5, which regulates caspase activation and apoptosis. Conclusion: Our data, in the context of a recent clinical trial in severe COVID-19, suggest benefits to further exploration of defibrotide and these pathways in COVID-19 and related endotheliopathies. Highlights: Defibrotide is FDA and EMA approved for treatment of veno-occlusive disease. Veno-occlusive disease shares features of thrombotic microangiopathy including COVID-19. TMA and COVID-19 patient plasma induced endothelial cell activation/injury in vitro. Defibrotide blocked these plasma-mediated effects at clinically appropriate doses. RNAseq identified pathways linked to COVID-19 endothelial injury blocked by defibrotide.